Research methods for education - Newby, Peter (New York : Routledge, 2014)
Written with the novice educational researcher in mind, this book is designed to help students produce good quality, valid and valuable research. The text is written in an engaging style and adopts a mixed-methods approach. It also features guidance on analytical procedures that require more advanced tools.
Sadrži bibliografiju i kazalo.
Keywords: Education -- Research -- Methodology; Education -- Research -- Methodology